The cycle of customer value: a model integrating customer and firm perspectives - Martelo-Landroguez, Silvia; Barroso-Castro, Carmen; Cepeda, Gabriel (Journal of Business Economics and Management, 2014)
The aim of this paper is to contribute to the strategic management literature by identifying a relationship between customer value seen from the customer perspective and customer value seen from the firm perspective, and how this relationship might affect the value created for the customer. We propose that such a relationship exists, and attempt to create an integrated view of customer value. We have not found any papers that focus on the relationship between these two perspectives of customer value, and our aim is to bridge this gap in the literature. Thus, the authors test, in a quantitative study utilizing structural equation models (SEM), how a firm should create value in order to be perceived by the customers, and how this value could be appropriated in the international banking industry. The results show to the managers that value creation impacts on perceived value but not on value appropriation.